The Effectiveness of Hippotherapy to Recover Gross Motor Function in Children with Cerebral Palsy: A Systematic Review and Meta-Analysis - Laura De Guindos-Sanchez; David Lucena-Anton; Jose A. Moral-Munoz; Alejandro Salazar; Ines Carmona-Barrientos (MDPI AG, 2020)
Cerebral palsy (CP) is a permanent disorder of the posture and movement, which can result in impairments of gross motor function, among others. Hippotherapy (HPT) is an emerging intervention to promote motor recovery in patients with neurological disorders, providing a smooth, precise, rhythmic, and repetitive pattern of movement to the patient. The main objective of this systematic review and meta-analysis of randomized controlled clinical trials was to analyze the effectiveness of HPT interventions on gross motor function in subjects with CP. The following databases were searched in May 2019: PubMed, Scopus, Embase, and Web of Science. The methodological quality of the randomized controlled trials was assessed using the Physiotherapy Evidence Database (PEDro) scale. A total of 10 studies were analyzed in this review, involving 452 participants. Favorable effects were obtained on the gross motor function (Gross Motor Function Measure-66, standardized mean difference (SMD) = 0.81, 95% confidence interval (CI) = 0.47-1.15, Gross Motor Function Measure-88 dimension A SMD = 0.64, 95% CI = 0.30-0.97, dimension B SMD = 0.42, 95% CI = 0.09-0.75, and dimension E SMD = 0.40, 95% CI = 0.06-0.73). The results obtained in the present review show the potential benefit of HPT intervention in improving gross motor function in children with CP.